2018
DOI: 10.7819/rbgn.v0i0.3954
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Regulatory Focus: Resist impulse consumption or let it happen?

Abstract: Purpose -The central objective of this research was to analyze the moderating role of chronic regulatory focus in impulse consumption when individuals are exhausted of self-control energies (ego depletion). In addition, we sought to examine the relationship between regulatory adjustment and the affective and cognitive processes of impulse decision making.Design/methodology/approach -The study was performed through an experiment. Data analysis was done using the Johnson-Neyman floodlight technique, which is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…So far, it was pointed out that there was a strong differentiation between promotion and prevention orientations in the context of decision-making (e.g. Costa et al. , 2018; Xu and Chen, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, it was pointed out that there was a strong differentiation between promotion and prevention orientations in the context of decision-making (e.g. Costa et al. , 2018; Xu and Chen, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the initial part of the experiment, regulatory focus manipulation was carried out through the same procedure of Freitas and Higgins (2002) and Costa et al. (2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, there was evidence that reduction strategies and interventions could reduce impulse purchases (Dholakia, 2000). The literature on resistance to impulse buying demonstrated that several personality variables could restrain impulse buying, such as self‐control (Efendi et al, 2019; Iyer et al, 2020; Moayery et al, 2019; Sultan et al, 2012), prevention focus (Freitas da Costa et al, 2018), mindfulness (Dhandra, 2020), self‐monitoring (Sharma et al, 2010; Sultan et al, 2012) and dignity (Bandyopadhyay, 2020; Dhandra, 2020). Some of the situation variables that prevented impulse buying had a continuous mitigating impact (Dholakia et al, 2005; Sultan et al, 2012), experiences after impulse purchase (Mittal et al, 2018; Spiteri Cornish, 2020), and crowding in space (Bandyopadhyay, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%